1997
DOI: 10.1021/js9602453
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of α-Cyclodextrin-lnduced Hemolysis. 1. The Two-Step Extraction of Phosphatidylinositol from the Membrane

Abstract: It has been suggested that the interaction of cyclodextrins with the lipid components of the erythrocyte membranes is the determining factor in the hemolysis induced by these cyclic oligosaccharides. In the case of alpha-cyclodextrin (cyclomaltohexose), phospholipids have been identified as the cell target. In our study, evidence for the interaction between alpha-cyclodextrin and different phospholipids has been obtained using synthetic membranes. Since phosphatidylinositol (PI) showed the strongest affinity f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
50
0
1

Year Published

2001
2001
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(52 citation statements)
references
References 33 publications
1
50
0
1
Order By: Relevance
“…In addition, a-CyD is reported to interact with phosphatidylinositol strongly, but not phosphatidylcholine. 26,27) Furthermore, Miyajima et al 28) and Nishijo et al 29) reported that a-CyD sequesters DPPC molecules from the liposomes and forms an inclusion complex with DPPC out of a membrane matrix. Thus, the mode of the interactions between a-CyD and G 2 -a-CyD and lipids in the biological membranes seems to be complicated.…”
Section: Release Of Membrane Componentsmentioning
confidence: 99%
“…In addition, a-CyD is reported to interact with phosphatidylinositol strongly, but not phosphatidylcholine. 26,27) Furthermore, Miyajima et al 28) and Nishijo et al 29) reported that a-CyD sequesters DPPC molecules from the liposomes and forms an inclusion complex with DPPC out of a membrane matrix. Thus, the mode of the interactions between a-CyD and G 2 -a-CyD and lipids in the biological membranes seems to be complicated.…”
Section: Release Of Membrane Componentsmentioning
confidence: 99%
“…CDs have been reported to interact with cell membrane constituents such as cholesterol, phospholipids, and phosphatidylinositols, resulting in the induction of hemolysis of RBC (25)(26)(27)(28). The magnitude of the hemolytic activity of the parent CDs is reported to increase in the order of γ-CD<α-CD<β-CD (25).…”
Section: Introductionmentioning
confidence: 99%
“…Cyclodextrins are also used in the cosmetics industry to create longer lasting fragrances and prevent the oxidation and degradation of oils (5). Laboratory applications include using cyclodextrins as size-exclusion columns, as artificial chaperones to remove detergents and facilitate the refolding of recombinant proteins (7,8), as a vehicle to develop molecular machines (9), and as a means for the delivery and removal of lipids from membranes to study bilayers and lipid rafts (10-13).We have taken advantage of the ability of cyclodextrins to bind lipids (11,12,14) and deliver them to cells (13) and asked whether cyclodextrin could be used to deliver inositol phospholipids to recombinant lipid kinases for in Abbreviations: At PIPK1, Arabidopsis thaliana phosphatidylinositol phosphate kinase 1; ␣ CD, ␤ CD, and ␥ CD, ␣ -, ␤ -, and ␥ -cyclodextrin; GST, glutathione-S -transferase; NBD-PtdInsP, d ( ϩ )-sn -1-O -[1- [6 Ј -[6-[(7-nitrobenz-2-oxa-1,3-diazol-4-yl) …”
mentioning
confidence: 99%
“…We have taken advantage of the ability of cyclodextrins to bind lipids (11,12,14) and deliver them to cells (13) and asked whether cyclodextrin could be used to deliver inositol phospholipids to recombinant lipid kinases for in Abbreviations: At PIPK1, Arabidopsis thaliana phosphatidylinositol phosphate kinase 1; ␣ CD, ␤ CD, and ␥ CD, ␣ -, ␤ -, and ␥ -cyclodextrin; GST, glutathione-S -transferase; NBD-PtdInsP, d ( ϩ )-sn -1-O -[1- [6 Ј -[6-[(7-nitrobenz-2-oxa-1,3-diazol-4-yl) …”
mentioning
confidence: 99%
See 1 more Smart Citation